Biocalcification by halophilic bacteria for remediation of concrete structures in marine environment. (1st November 2016) - Bansal, Roohi; Dhami, Navdeep Kaur; Mukherjee, Abhijit; Reddy, M Sudhakara
Abstract: Microbial carbonate precipitation has emerged as a promising technology for remediation and restoration of concrete structures. Deterioration of reinforced concrete structures in marine environments is a major concern due to chloride-induced corrosion. In the current study, halophilic bacteria Exiguobacterium mexicanum was isolated from sea water and tested for biomineralization potential under different salt stress conditions. The growth, urease and carbonic anhydrase production significantly increased under salt stress conditions. Maximum calcium carbonate precipitation was recorded at 5 % NaCl concentration. Application of E. mexicanum on concrete specimens significantly increased the compressive strength (23.5 %) and reduced water absorption about five times under 5 % salt stress conditions compared to control specimens. SEM and XRD analysis of bacterial-treated concrete specimens confirmed the precipitation of calcite. The present study results support the potential of this technology for improving the strength and durability properties of building structures in marine environments.